The Effect of Using Online Learning Media on Student Satisfaction at the School of Multi Media "MMTC" Yogyakarta - Dhety Chusumastuti; Shafira Meilissa Eka Putri (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
The use of learning media is currently the most important aspect that deserves attention during the learning process, especially since the beginning of the outbreak of the new virus, namely COVID-19 which originated from China. Since the end of 2019, the World Health Organization (WHO) has designated this as a pandemic that has hit the world or a global pandemic. The pandemic caused the way of learning to change from what was originally conventional to online learning, this caused various reactions from students. Therefore, the purpose of this study was to determine how much influence the use of online learning media had on student satisfaction at STMM Yogyakarta. This study uses the EUCS method to measure the dimensions of satisfaction by Doll & Torkzadeh and the concept of seven dimensions of ACTIONS media utilization by A. W. (Tony) Bates. The method used in this research is quantitative research. The samples taken were active students of STMM Yogyakarta as many as 95 people. The data collection technique used a questionnaire distributed via google form. The data analysis method in this study uses Simple Linear Regression, Coefficient of Determination (R Square) and t-test. Data processing using SPSS 24.00 software for Windows. The results of this study indicate that the use of online learning has an effect on student satisfaction of 89% while the rest is influenced by other variables.